Phosphorylated and Non-phosphorylated Leucine Rich Amelogenin Peptide Differentially Affect Ameloblast Mineralization - Le Norcy, Elvire; Lesieur, Julie; Sadoine, Jeremy; Rochefort, Gaël Y.; Chaussain, Catherine; Poliard, Anne (Frontiers in Physiology, 2018)
The Leucine Rich Amelogenin Peptide (LRAP) is a product of alternative splicing of the amelogenin gene. As full length amelogenin, LRAP has been shown, in precipitation experiments, to regulate hydroxyapatite (HAP) crystal formation depending on its phosphorylation status. However, very few studies have questioned the impact of its phosphorylation status on enamel mineralization in biological models. Therefore, we have analyzed the effect of phosphorylated (+P) or non-phosphorylated (−P) LRAP on enamel formation in ameloblast-like cell lines and ex vivo cultures of murine postnatal day 1 molar germs. To this end, the mineral formed was analyzed by micro-computed tomography, Field Emission Scanning Electron Microscopy, Transmission Electron Microscopy, Selected Area Electon Diffraction imaging. Amelogenin gene transcription was evaluated by qPCR analysis. Our data show that, in both cells and germ cultures, LRAP is able to induce an up-regulation of amelogenin transcription independently of its phosphorylation status. Mineral formation is promoted by LRAP(+P) in all models, while LRAP(–P) essentially affects HAP crystal formation through an increase in crystal length and organization in ameloblast-like cells. Altogether, these data suggest a differential effect of LRAP depending on its phosphorylation status and on the ameloblast stage at the time of treatment. Therefore, LRAP isoforms can be envisioned as potential candidates for treatment of enamel lesions or defects and their action should be further evaluated in pathological models.